1996
DOI: 10.1159/000188831
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Lipoprotein(a) in Continuous Ambulatory Peritoneal Dialysis Is Related to Peritoneal Transport of Proteins and Glucose

Abstract: Markedly increased plasma lipoprotein(a) [Lp(a)] levels have recently been reported in continuous ambulatory peritoneal dialysis (CAPD) patients but the genesis is obscure. Lp(a) levels in CAPD are in general higher than in hemodialysis (HD) patients, suggesting that the dialysis procedure might be of importance. In the present study, we investigated relationships between Lp(a) and parameters related to the dialysis procedure per se (dialysis dose, peritoneal glucose absorption, protein losses and protein clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 34 publications
4
29
1
Order By: Relevance
“…28,29 This heightened risk might be attributed to many factors including lose of proteins via peritoneal membrane, increased absorption of glucose from dialysate and increased serum levels of insulin in this population. 30 In accordance to these study results, usage of icodextrincontaining dialysis solutions was found to be superior to glucose-containing dialysis solutions in terms of lowering serum triglycerides and small dense LDL concentrations. 31 EAT, like abdominal visceral adipose tissue, is a metabolically active tissue that can secrete proinflammatory cytokines and utilize free fatty acids (FFAs).…”
Section: Discussionsupporting
confidence: 78%
“…28,29 This heightened risk might be attributed to many factors including lose of proteins via peritoneal membrane, increased absorption of glucose from dialysate and increased serum levels of insulin in this population. 30 In accordance to these study results, usage of icodextrincontaining dialysis solutions was found to be superior to glucose-containing dialysis solutions in terms of lowering serum triglycerides and small dense LDL concentrations. 31 EAT, like abdominal visceral adipose tissue, is a metabolically active tissue that can secrete proinflammatory cytokines and utilize free fatty acids (FFAs).…”
Section: Discussionsupporting
confidence: 78%
“…High serum levels of Lp (a) in PD patients may be due to increased hepatic synthesis of Lp (a) following loss of amino acids and proteins through PD (5,22,37,43,44). In our study, ginger consumption had no significant effect on serum Lp (a).…”
Section: Discussioncontrasting
confidence: 53%
“…[28] Markedly elevated Lp(a) levels in CAPD patients have been reported. [2,29,30] A correlation between Lp(a) and peritoneal glucose absorption was reported, indicating that the increased plasma Lp(a) levels in CAPD may be related to the dialysis procedure, particularly peritoneal transport of proteins and glucose. In this study, no significant difference in Lp(a) levels between the three groups was observed.…”
Section: Discussionmentioning
confidence: 99%